A study on effect of gender ideology on work and family responsibilities amongst medical professionals. - Tan, Yee Yee. (2010)
Reconciling work and family is a major challenge for female doctors. Women remain as the primary caretaker of the children despite their high-status professional careers. The tension between dual roles of mothers and professionals lead some female doctors to trade-off various priorities in their lives in order to spend more time with their children. This qualitative study aims to investigate the lived experience of stay-at home mothers and also the perspective of the male doctors in the work-family juggling act using individual in-depth interviews. The dominant themes encompassed the decision for doctors to stay home, the perceived benefit and how their personal values play an important role in their decision-making process. Findings indicate that family care giving as the main responsibility of women remains despite their professional training and high level of education.